Elotuzumab plus lenalidomide/dexamethasone for relapsed or refractory multiple myeloma: ELOQUENT‐2 follow‐up and post‐hoc analyses on progression‐free survival and tumour growth. (5th July 2017) - Dimopoulos, Meletios A.; Lonial, Sagar; White, Darrell; Moreau, Philippe; Palumbo, Antonio; San‐Miguel, Jesus; Shpilberg, Ofer; Anderson, Kenneth; Grosicki, Sebastian; Spicka, Ivan; Walter‐Croneck, Adam; Magen, Hila; et al.
Summary: The randomized phase III ELOQUENT‐2 study (NCT01239797) evaluated the efficacy and safety of elotuzumab + lenalidomide/dexamethasone (ELd) versus lenalidomide/dexamethasone (Ld) in relapsed/refractory multiple myeloma. ELd reduced the risk of disease progression/death by 30% versus Ld (hazard ratio [HR] 0·70). Median time from diagnosis was 3·5 years. We present extended 3‐year follow‐up data. Endpoints included progression‐free survival (PFS), overall response rate (ORR) and interim overall survival (OS). Exploratory post‐hoc analyses included impact of time from diagnosis and prior lines of therapy on PFS, and serum M‐protein dynamic modelling. ORR was 79% (ELd) and 66% (Ld) ( P = 0·0002). ELd reduced the risk of disease progression/death by 27% versus Ld (HR 0·73; P = 0·0014). Interim OS demonstrated a trend in favour of ELd ( P = 0·0257); 1‐, 2‐ and 3‐year rates with ELd versus Ld were: 91% versus 83%, 73% versus 69% and 60% versus 53%. In patients with ≥ median time from diagnosis and one prior therapy, ELd resulted in a 53% reduction in the risk of progression/death versus Ld (HR 0·47). Serum M‐protein dynamic modelling showed slower tumour regrowth with ELd. Adverse events were comparable between arms. ELd provided a durable and clinically relevant improvement in efficacy, with minimal incremental toxicity.